Photocatalytic ceramic membrane preparation method and integrated photocatalytic ceramic membrane water treatment device

By combining the modified graphene oxide-titanium oxide composite nanoparticle ceramic film with UV-LED light source, the integration of film retention and photocatalytic degradation of the photocatalytic water treatment device is achieved, and catalyst recovery and small molecule organic micropollutant removal is solved. The problem has improved the water treatment efficiency and the environmental protection of the device.

CN113262649BActive Publication Date: 2024-12-13TSINGHUA UNIVERSITY
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202110680638.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-06-18
Publication Date
2024-12-13
Estimated Expiration
2041-06-18

AI Technical Summary

Technical Problem

The existing photocatalytic technology faces problems such as difficulty in recovering catalysts, limited effects of non-permeable supported catalysts, difficulty in removing intermediate products of photocatalytic degradation, and the toxicity, fragility and large land area of ​​traditional ultraviolet mercury lamps, and micro-pollution of small molecules Inefficient removal of objects.

Method used

By preparing graphene oxide-titanium oxide composite nanoparticle modified ceramic film, combined with UV-LED light source activation, an integrated water treatment device is realized for film interception and photocatalytic degradation, and the nanoparticle coating of the modified ceramic film is used to improve catalytic performance and Structural stability enhances the removal and degradation of organic micropollutants.

Benefits of technology

The catalyst separation and recycling is realized, the removal rate and degradation efficiency of organic micropollutants are improved, and the advantages of small footprint, energy saving and flexible design are provided. It solves the toxicity and fragility problems of traditional technology, and improves the water treatment process. intensification and efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN113262649B_ABST
    Figure CN113262649B_ABST
Patent Text Reader

Abstract

The present invention discloses a method for preparing a photocatalytic ceramic membrane and an integrated photocatalytic ceramic membrane water treatment device. A graphene oxide-titanium oxide composite nanoparticle dispersion is prepared so that the doping amount of the graphene oxide therein is greater than 0 and less than 10%. The composite nanoparticles are then bonded to a ceramic diaphragm by a vacuum filtration method to form a modified ceramic diaphragm with a nanoparticle coating, and its performance is enhanced by a heat treatment of >160°C to obtain a photocatalytic ceramic membrane. The device includes an integrated UV-membrane processing unit, which includes a UV light source and a photocatalytic ceramic membrane, and enables the UV light source to directly irradiate the photocatalytic ceramic membrane to achieve photocatalytic activation. The present invention has the advantages of integration of membrane filtration and catalytic degradation, flexible reactor design, small footprint, and energy saving.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a photocatalytic ceramic film preparation method and an integrated photocatalytic ceramic film water treatment device, belonging to the technical field of environmental protection. Background Art

[0002] In recent years, due to the increasingly serious water pollution, the emerging organic micropollutants (OMPs) released into water bodies have attracted widespread attention. Membrane technology, as an emerging water treatment technology, has the advantages of small footprint and high treatment efficiency. Compared with organic membranes, inorganic ceramic membranes have the characteristics of high membrane flux, strong chemical stability and mechanical strength, anti-pollution, and long service life. They are more advantageous when combined with advanced oxidation processes (AOPs) and have gradually attracted attention in the field of water treatment in recent years. Commercial ceramic membranes are microfiltration membranes and ultrafiltration membranes, which have high removal rates for turbidity and microorganisms in water bodies, but low removal rates for inorganic ions, dissolved organic matter, and especially small molecular organic micropollutants. In addition, membrane technology also has problems such as membrane pollution and concentrated water treatment.

[0003] Photocatalytic advanced oxidation process is an efficient and green treatment process, which is mostly used to degrade refractory organic pollutants in sewage and achieve zero discharge of water treatment. However, photocatalytic technology mainly faces the following problems: (1) It is difficult to recover the catalyst from the treated solution; (2) The effect of non-permeable supported catalyst is limited by mass transfer; (3) The removal of photocatalytic degradation intermediates. At the same time, photocatalytic technology generally uses traditional ultraviolet mercury lamps as light sources, which have problems such as toxicity (containing mercury), fragility, large footprint, and difficulty in reactor design. Ultraviolet light-emitting diodes (UV-LEDs), as a new type of ultraviolet light source, are increasingly attracting research attention in the field of water treatment. The advantages of UV-LEDs include concentrated wavelength, smaller footprint, flexible design, longer service life, environmental friendliness (mercury-free), shorter startup time, and the ability to be turned on and off at high frequencies. The development of UV-LEDs has opened up new possibilities for water treatment and photocatalytic reactor design. There have been many studies on titanium oxide (TiO2) photocatalytic films, but how to further modify TiO2-based photocatalytic films so that they can be used for UV-LED light source activation has only gradually attracted attention in recent years. Summary of the invention

[0004] The present invention aims to provide a method for preparing a photocatalytic ceramic membrane which has both membrane retention performance and photocatalytic degradation performance through GO-TiO2 modification, and also provides a water treatment device using the modified photocatalytic ceramic membrane. UV-LED and the prepared modified photocatalytic ceramic membrane constitute an integrated photocatalytic ceramic membrane water treatment device, and the photocatalytic effect of the photocatalytic ceramic membrane is stimulated by a UV-LED light source, so that the modified photocatalytic ceramic membrane has both membrane retention and photocatalytic degradation effects, thereby achieving the removal and degradation of organic micropollutants with different characteristics.

[0005] The present invention is achieved through the following technical solutions:

[0006] A method for preparing a photocatalytic ceramic film, comprising:

[0007] Preparing a graphene oxide (GO)-titanium oxide (TiO2) composite nanoparticle dispersion, wherein the doping amount of graphene oxide (GO) is greater than 0 and less than 10%;

[0008] Ceramic diaphragm pretreatment: Pretreatment includes cleaning and drying;

[0009] The graphene oxide-titanium oxide composite nanoparticle dispersion is combined with the ceramic membrane by vacuum filtration to form a rough modified ceramic membrane with a nanoparticle coating, and then the surface of the rough modified ceramic membrane is rinsed with deionized water and placed in an oven at 40°C-70°C for 10-30 minutes;

[0010] The dried crude modified ceramic membrane is placed in a muffle furnace, the temperature is increased to >160°C at a heating rate of 1-5°C / min, and the heating is continued for 1-3h; a photocatalytic ceramic membrane with a nanoparticle coating thickness of 0.1-1μm is obtained.

[0011] Optionally, according to an embodiment of the present invention, in the above technical solution, the graphene oxide-titanium oxide composite nanoparticle dispersion is prepared by a hydrothermal method, comprising:

[0012] The graphene oxide nanoparticles were dispersed by ultrasonic for 20-30 min and separated by centrifugation to obtain a GO dispersion;

[0013] The GO dispersion was heated by shaking at 50-70° C., and (NH 4 ) 2 TiF 6 and H 3 BO 3 were added to an appropriate amount of the GO dispersion at a molar ratio of 1:3, and the shaking heating was continued for 2-3 h to obtain a GO-TiO 2 composite nanoparticle dispersion.

[0014] Optionally, according to an embodiment of the present invention, in the aforementioned technical solution, the ceramic diaphragm pretreatment includes: rinsing the ceramic diaphragm with acetone and high-purity water in sequence, and placing it in a 40°C-70°C oven for drying for 10-30 minutes after rinsing.

[0015] Optionally, according to an embodiment of the present invention, in the aforementioned technical solution, the vacuum filtration method is set according to a vacuum degree of 0.5-0.8Mpa and a filtration time of 5-15min.

[0016] An integrated photocatalytic ceramic membrane water treatment device includes an integrated UV-membrane treatment unit, the integrated UV-membrane treatment unit includes a UV light source and a membrane assembly, the membrane assembly includes a chamber and a photocatalytic ceramic membrane arranged in the chamber, the photocatalytic ceramic membrane is prepared according to the above-mentioned method; the UV light source is arranged outside the chamber and is arranged so as to be able to directly irradiate the photocatalytic ceramic membrane.

[0017] Optionally, according to an embodiment of the present invention, in the aforementioned technical solution, the UV light source is a UV-LED light-emitting device.

[0018] Optionally, according to an embodiment of the present invention, in the aforementioned technical solution, a quartz window is provided on the wall of the chamber adjacent to the UV light source.

[0019] The beneficial effects and advantages of the present invention include:

[0020] 1) Modified ceramic membrane Using a ceramic membrane with a large flux as a carrier of the photocatalyst (TiO2) can solve the problem of catalyst separation and recovery.

[0021] 2) The integrated UV-membrane treatment unit can utilize the high efficiency of the membrane itself to intercept negatively charged organic micropollutants, while realizing the photocatalytic activation of UV-LED, enhancing the removal of uncharged pollutants through photocatalysis; it can realize membrane filtration and photocatalytic degradation at the same time, and catalytic degradation occurs simultaneously on the membrane surface and in the membrane pores, which increases the residence time of pollutant degradation and increases mass transfer efficiency.

[0022] 3) The water treatment device including the integrated UV-membrane treatment unit realizes the intensification of the water treatment process flow, and has the advantages of small footprint, flexible reactor design, and energy saving. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 It is the X-ray diffraction spectrum of the composite nanoparticles in the embodiment involved in the present invention.

[0024] Figure 2 This is a scanning electron microscope image of the photocatalytic ceramic film of Example 2.

[0025] Figure 3It is a schematic diagram of the integrated photocatalytic ceramic membrane water treatment device involved in the present invention.

[0026] Figure 4 Schematic diagram of the removal effect on carbamazepine, naproxen and diclofenac.

[0027] In the figure: 1 - water inlet assembly; 2 - membrane assembly; 3 - UV light source; 4 - water outlet assembly. DETAILED DESCRIPTION

[0028] In order to make the purpose, technical solution and advantages of the embodiments of the present application clearer, the technical solution in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of this application.

[0029] In addition, “step S1”, “step S2”, etc. are only used for description purposes. Unless otherwise specified, the steps in the method of the present invention are not necessarily performed in the order listed, but may be performed in any order.

[0030] The catalytic performance of TiO2 in TiO2-based photocatalytic membranes has always been the key to photocatalytic technology, and GO modification can improve the retention performance of the membrane and increase the structural stability of the membrane. The oxygen-containing functional groups of GO can be used to fix TiO2 to reduce the aggregation of nanocomposites, and GO loading can reduce the mesoporosity of TiO2 and increase its surface functional groups, thereby increasing the adsorption of pollutants on the surface of the material. GO-TiO2 modified ceramic membranes can increase the negative charge of the membrane surface, enhance the photocatalytic effect through the physical interception effect of the membrane, and improve the photocatalytic effect of TiO2.

[0031] The following examples obtain different modified ceramic membranes by changing the doping ratio of GO (referring to the mass percentage of GO in the GO-TiO2 composite nanoparticle dispersion, i.e., wt.%, simplified as %) and / or the heat treatment temperature.

[0032] Step S1: preparing a graphene oxide (GO)-titanium oxide (TiO2) composite nanoparticle dispersion, wherein the doping amount (doping ratio) of graphene oxide (GO) is greater than 0 and less than 10%.

[0033] Graphene oxide nanoparticles with a lamellar structure are usually selected. The graphene oxide nanoparticles are dispersed by ultrasonic for 20-30 minutes and centrifuged to obtain a GO dispersion. The GO dispersion is heated at 50-70°C, and (NH4)2TiF6 and H3BO3 are added to an appropriate amount of the GO dispersion at a molar ratio of 1:3, and the oscillation heating is continued for 2-3 hours to allow TiO2 to grow in situ on the GO nanoparticles with a lamellar structure, thereby obtaining a GO-TiO2 composite nanoparticle dispersion.

[0034] The ceramic membrane is a commercial ceramic ultrafiltration membrane, and is pretreated before being coated with the composite nanoparticle layer.

[0035] Step S2: Ceramic diaphragm pretreatment: The ceramic diaphragm is rinsed with acetone and high-purity water in turn, and then placed in a 40°C-70°C oven for drying for 10-30 minutes.

[0036] Step S3: coating a composite nanoparticle layer. The graphene oxide-titanium oxide composite nanoparticle dispersion is bonded to the ceramic membrane by vacuum filtration to form a coarse modified ceramic membrane with a nanoparticle coating (also called a nano-modified layer), and then the surface of the coarse modified ceramic membrane is rinsed with deionized water to remove the weakly bonded nanoparticles on the surface, and then placed in a 40°C-70°C oven to dry for 10-30 minutes.

[0037] Step S4: Heat treatment: The dried coarse modified ceramic membrane is placed in a muffle furnace, and the temperature is raised to >160°C at a heating rate of 1-5°C / min, and the heating is continued for 1-3h to increase the bonding strength of the nanoparticle coating itself and the ceramic membrane.

[0038] After heat treatment, a photocatalytic ceramic film with a nanoparticle coating thickness of 0.1-1 μm is obtained.

[0039] The preferred preparation conditions of the photocatalytic ceramic film are as follows: a GO doping amount of 1.6%-5.5% and a heat treatment temperature of 260-360°C.

[0040] Comparative Example 1: 0% GO-360°C.

[0041] Step S1: Add 0.1 mol / L (NH4)2TiF6 and 0.3 mol / L H3BO3 into 10 mL of deionized water, heat and shake at 60°C and maintain for 2 h to obtain a TiO2 nanoparticle dispersion.

[0042] Step S2: Select a commercial ceramic ultrafiltration membrane, first rinse the ceramic membrane with acetone, then rinse with high-purity water, and finally take it out and put it in a 50°C oven to dry for 15 minutes.

[0043] Step S3: The nanoparticle dispersion obtained in step S1 is then loaded onto the surface of the ceramic membrane pretreated in step S2 by vacuum filtration (0.5 MPa) to obtain a coarsely modified ceramic membrane, and then the surface of the coarsely modified ceramic membrane is rinsed with deionized water and dried in an oven at 50°C for 15 minutes.

[0044] Step S4: Place the roughly modified ceramic membrane dried in step S3 into a muffle furnace and heat it, raising the temperature to 360° C. at a heating rate of 2° C. / min, and continue heating at this temperature for 2 hours, then take it out and cool it to room temperature.

[0045] The obtained modified ceramic diaphragm is a pure TiO2 modified ceramic diaphragm without GO, which is used as comparative example 1 and is recorded as 0% GO-360°C.

[0046] Comparative Example 2: 1.6% GO-160°C (Li, C. et al., Chemical Engineering Journal, 2019.378: p.122138).

[0047] Step S1: Weigh 1.44 mg of GO nanoparticles and disperse them ultrasonically for 30 min, then centrifuge at 8000 rpm to remove large agglomerates so that they are evenly dispersed in the aqueous solution. Add 0.1 mol / L (NH4)2TiF6 and 0.3 mol / L H3BO3 to 10 mL of GO dispersion, at which the doping amount of GO is 1.6%, and heat and shake the GO dispersion at 60 ° C and keep it for 2 h.

[0048] Step S2: Select a commercial ceramic ultrafiltration membrane, first rinse the ceramic membrane with acetone, then rinse with high-purity water, and finally take it out and put it in a 50°C oven to dry for 15 minutes.

[0049] Step S3: The nanoparticle dispersion obtained in step S1 is then loaded onto the surface of the ceramic membrane pretreated in step S2 by vacuum filtration (0.5 MPa) to obtain a coarsely modified ceramic membrane, and then the surface of the coarsely modified ceramic membrane is rinsed with deionized water and dried in an oven at 50°C for 15 minutes.

[0050] Step S4: Place the roughly modified ceramic membrane dried in step S3 into a muffle furnace and heat it at a heating rate of 2°C / min to 160°C, and continue heating at this temperature for 2 hours, then take it out and cool it to room temperature.

[0051] The obtained modified ceramic diaphragm is used as comparative example 2 and is recorded as 1.6% GO-160°C.

[0052] Example 1: 1.6% GO-260°C.

[0053] Steps S1 to S3 are the same as those in Comparative Example 2.

[0054] Step S4: Place the roughly modified ceramic membrane dried in step S3 into a muffle furnace and heat it at a heating rate of 2°C / min to 260°C, and continue heating at this temperature for 2 hours, then take it out and cool it to room temperature.

[0055] The obtained modified ceramic diaphragm is used as Example 1 and is recorded as 1.6% GO-260°C.

[0056] Example 2: 1.6% GO-360°C.

[0057] Steps S1 to S3 are the same as those in Comparative Example 2.

[0058] Step S4: Place the roughly modified ceramic membrane dried in step S3 into a muffle furnace and heat it, raising the temperature to 360° C. at a heating rate of 2° C. / min, and continue heating at this temperature for 2 hours, then take it out and cool it to room temperature.

[0059] The obtained modified ceramic diaphragm is used as Example 2 and is recorded as 1.6% GO-360°C.

[0060] Example 3: 2.7% GO-360°C.

[0061] Step S1: Weigh 2.78 mg of GO nanoparticles and disperse them ultrasonically for 30 min, then centrifuge at 8000 rpm to remove large agglomerates so that they are evenly dispersed in the aqueous solution. Add 0.1 mol / L (NH4)2TiF6 and 0.3 mol / L H3BO3 to 10 mL of GO dispersion, and the doping amount of GO is 2.7%. The GO dispersion is heated and shaken at 60°C and maintained for 2 h.

[0062] Steps S2 to S4 are the same as those in Example 2.

[0063] The obtained modified ceramic diaphragm is used as Example 3 and is recorded as 2.7% GO-360°C.

[0064] Example 4: 5.5% GO-360°C.

[0065] Step S1: Weigh 5.81 mg of GO nanoparticles and disperse them ultrasonically for 30 min. Then, centrifuge at 8000 rpm to remove large agglomerates so that they are evenly dispersed in the aqueous solution. Add 0.1 mol / L (NH4)2TiF6 and 0.3 mol / L H3BO3 to 10 mL of GO dispersion, and the doping amount of GO is 5.5%. The GO dispersion is heated and shaken at 60°C and maintained for 2 h.

[0066] Steps S2 to S4 are the same as those in Example 2.

[0067] The obtained modified ceramic diaphragm is used as Example 4 and is recorded as 5.5% GO-360°C.

[0068] Example 5: 10% GO-360°C.

[0069] Step S1: Weigh 10 mg of GO nanoparticles and disperse them ultrasonically for 30 minutes. Then, centrifuge at 8000 rpm to remove large aggregates so that they are evenly dispersed in the aqueous solution. Add 0.1 mol / L (NH4)2TiF6 and 0.3 mol / L H3BO3 to 10 mL of GO dispersion, and the doping amount of GO is 10%. The GO dispersion is heated and shaken at 60°C for 2 hours.

[0070] Steps S2 to S4 are the same as those in Example 2.

[0071] The obtained modified ceramic diaphragm is used as Example 5 and is recorded as 10% GO-360°C.

[0072] Table 1 is a summary of the GO doping amount (ratio) and heat treatment temperature in the preparation methods corresponding to the comparative examples and embodiments, and the performance comparison of the nanoparticles or composite nanoparticles (except for the comparative example 1 which is pure TiO2). The nanoparticles were obtained by filtering the GO-TiO2 composite nanoparticle dispersion through a 0.2μm filter membrane. The specific surface area and pore size of the nanoparticles were analyzed by N2 adsorption-desorption isotherms and BET pore size distribution curves. The crystallinity and grain size of the nanoparticles were analyzed by powder X-ray diffraction.

[0073] Table 1 Summary of key preparation conditions and nanoparticle properties of each comparative example and embodiment

[0074]

[0075] On the one hand, the increase in GO doping will produce a pore connectivity effect, increase the specific surface area and microporosity of the composite nanoparticles, and reduce the grain size (as shown in Table 1), thereby increasing the adsorption of pollutants and the generation of free radicals, which is beneficial to the photocatalytic reaction. Figure 1 As shown in the figure, with the increase of heating temperature, the X-ray diffraction peak intensity of the composite nanoparticles increases, the crystallinity increases, and the grain size decreases with the increase of heating temperature. However, the effects of increasing GO doping amount and increasing heat treatment temperature are not linear changes, but the result of the coupling of the two. Figure 2 It can be seen that GO-TiO2 composite nanoparticles are not only loaded on the surface of the photocatalytic ceramic film, but also distributed in the entire film structure.

[0076] Compared with Comparative Examples 1 and 2, the nanoparticles obtained in Examples 1 to 5 have larger pore size and specific surface area, and smaller grain size. Among them, Example 2 makes the nanoparticles have the largest pore size and the smallest grain size, as well as a larger specific surface area. The nanoparticles prepared in Example 3 have the largest specific surface area, as well as a larger pore size and a smaller grain size. The modified ceramic membrane loaded with nanomaterials having a larger pore size has a higher membrane flux. The modified ceramic membrane loaded with nanomaterials having a larger specific surface area and a smaller grain size is more conducive to photocatalytic reactions.

[0077] like Figure 3 As shown, an integrated photocatalytic ceramic membrane water treatment device includes an integrated UV-membrane treatment unit, which includes a UV light source 3 and a membrane assembly 2. The membrane assembly 2 includes at least a chamber and a group of photocatalytic ceramic membranes. The UV light source 3 is preferably a UV-LED light-emitting device. Usually, the chamber is arranged in a closed manner, and the UV light source is arranged on one side of the chamber (preferably the top of the chamber). The side wall of the chamber is provided with a quartz window that can transmit UV light, so that the UV light source can directly irradiate the photocatalytic ceramic membrane to activate the photocatalytic effect of the photocatalytic ceramic membrane. The device also includes a water inlet assembly 1 and a water outlet assembly 4 respectively arranged at both ends of the integrated UV-membrane treatment unit, which are used to feed water to be treated and discharge treated water respectively. The arrangement of the membrane assembly can be understood and imagined by those skilled in the art, and will not be described in detail here.

[0078] The modified photocatalytic ceramic membranes prepared in Example 2 and Example 3 were respectively placed in the membrane assembly 2, and an integrated UV-membrane treatment unit was formed with a UV-LED light-emitting device (light-emitting wavelength 365nm, power 14.4W), as Example 6 and Example 7, respectively. The removal effect was investigated by taking slightly polluted water containing carbamazepine (CBZ) as the influent, and compared with Comparative Example 2, it was found that when the comparative example degraded CBZ, k was 0.005min -1 , k is the pseudo-first-order reaction kinetic constant. The k values ​​of Example 6 and Example 7 when degrading CBZ were significantly improved, which were 0.018min and 0.025min, respectively. -1 、0.015min -1 This means that the embodiment has a more obvious photocatalytic degradation effect than the comparative example.

[0079] The device described in Example 6 was further used to test its effect of degrading organic micro-polluted water containing negatively charged naproxen (NAP) and diclofenac (DCF). Figure 4 As shown, under the synergistic effect of membrane retention and photocatalytic degradation, the device can achieve a 90% removal rate for CBZ and a 100% removal rate for NAP and DCF.

[0080] System energy consumption is an important economic factor in water treatment. This device uses a UV-LED light-emitting device (light-emitting wavelength 365nm, power 14.4W) as the light source. The power consumption required for photocatalytic degradation of 90% CBZ is about 800kWh / m 3 The power consumption of using a traditional low-pressure mercury lamp (luminous wavelength 254nm, power 172W) as a light source is about 10395kWh / m 3 UV-LEDs are more efficient and energy-efficient than traditional low-pressure mercury lamps in photocatalytic degradation of organic micropollutants.

[0081] The results show that the modified ceramic membrane prepared in the above examples has an obvious photocatalytic degradation effect and is a photocatalytic ceramic membrane. The integrated photocatalytic ceramic membrane water treatment device with a UV-LED light-emitting device as a UV light source can simultaneously achieve membrane filtration and photocatalytic degradation, and save energy.

[0082] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A method for preparing a photocatalytic ceramic film, characterized in that: include: A graphene oxide-titanium oxide composite nanoparticle dispersion is prepared, wherein the doping amount of the graphene oxide is greater than 0 and less than 10%; the graphene oxide-titanium oxide composite nanoparticle dispersion is prepared by a hydrothermal method, comprising: The graphene oxide nanoparticles were dispersed by ultrasonic for 20-30 min and separated by centrifugation to obtain a GO dispersion; The GO dispersion is heated by shaking at 50-70° C., and (NH4)2TiF6 and H3BO3 are added to an appropriate amount of the GO dispersion in a molar ratio of 1:3, and the shaking heating is continued for 2-3 hours to obtain a GO-TiO2 composite nanoparticle dispersion; Ceramic diaphragm pretreatment: Pretreatment includes cleaning and drying; The graphene oxide-titanium oxide composite nanoparticle dispersion is combined with the ceramic membrane by vacuum filtration to form a rough modified ceramic membrane with a nanoparticle coating, and then the surface of the rough modified ceramic membrane is rinsed with deionized water and placed in an oven at 40°C-70°C for 10-30 minutes; The dried crude modified ceramic membrane is placed in a muffle furnace, the temperature is increased to >160°C at a heating rate of 1-5°C / min, and the heating is continued for 1-3h; a photocatalytic ceramic membrane with a nanoparticle coating thickness of 0.1-1μm is obtained.

2. The method according to claim 1, characterized in that: The ceramic diaphragm pretreatment comprises: washing the ceramic diaphragm with acetone and high-purity water in sequence, and drying it in a 40° C.-70° C. oven for 10-30 minutes after washing.

3. The method according to claim 1, characterized in that The vacuum filtration method is set according to a vacuum degree of 0.5-0.8Mpa and a filtration time of 5-15min.

4. Integrated photocatalytic ceramic membrane water treatment device, characterized in that: It comprises an integrated UV-film processing unit, which comprises a UV light source and a film assembly, wherein the film assembly comprises a chamber and a photocatalytic ceramic film arranged in the chamber, wherein the photocatalytic ceramic film is prepared according to the method described in any one of claims 1 to 3; the UV light source is arranged outside the chamber and is arranged so as to be able to directly irradiate the photocatalytic ceramic film.

5. The device according to claim 4, characterized in that The UV light source is a UV-LED light emitting device.

6. The device according to claim 4, characterized in that A quartz window is provided on a wall of the chamber adjacent to the UV light source.

Citation Information

Patent Citations

  • Preparation method of graphene / titanium dioxide composite photocatalyst

    CN101890344A

  • Porous inorganic ceramic membrane-graphene-TiO2 photocatalyst composite material and its preparation method

    CN102728339A

  • Submerged photocatalytic ceramic membrane reactor

    CN1962044A

  • Integrated photocatalytic ceramic membrane water treatment device

    CN217909816U